The role of cardiorenal biomarkers for risk stratification in the early follow-up after hospitalisation for acute heart failure. (September 2013) - Tolonen, J.; Lassus, J. P. E.; Siirila-Waris, K.; Tarvasmäki, T.; Pulkki, K.; Sund, R.; Peuhkurinen, K.; Nieminen, M. S.; Harjola, V.-P.; ,
Abstract Context: Cardiorenal biomarkers (CBs) predict outcome in acute heart failure (AHF). Objective: To evaluate CBs in early follow-up prognostication. Methods: In 124 AHF patients, levels of CystatinC, NT-proBNP and TroponinI measured five weeks from admission (W5) and relative change from day 2 (D2) were assessed for 6-month prognosis (mortality/HF hospitalization). Results: The combined end-point occurred in 33 patients (27%). D2-, W5-cystatin≥ median, and lack of ≥30%decrease in NT-proBNP were independent predictors of outcome. Additionally, a risk score established from W5 CBs identified patients with very high event rate. Conclusions: CBs at early follow-up of AHF may guide risk stratification.